MSCs-Derived Exosomes and Neuroinflammation, Neurogenesis and Therapy of Traumatic Brain Injury - Yang, Yongxiang; Ye, Yuqin; Su, Xinhong; He, Jun; Bai, Wei; He, Xiaosheng (Frontiers in Cellular Neuroscience, 2017)
Exosomes are endosomal origin membrane-enclosed small vesicles (30–100 nm) that contain various molecular constituents including proteins, lipids, mRNAs and microRNAs. Accumulating studies demonstrated that exosomes initiated and regulated neuroinflammation, modified neurogenic niches and neurogenesis, and were even of potential significance in treating some neurological diseases. These tiny extracellular vesicles (EVs) can derive from some kinds of multipotent cells such as mesenchymal stem cells (MSCs) that have been confirmed to be a potentially promising therapy for traumatic brain injury (TBI) in experimental models and in preclinical studies. Nevertheless, subsequent studies demonstrated that the predominant mechanisms of MSCs’s contributions to brain tissue repairment and functional recovery after TBI were not the cell replacement effects but likely the secretion-based paracrine effects produced by EVs such as MSCs-derived exosomes. These nanosized exosomes derived from MSCs cannot proliferate, are easier to preserve and transfer and have lower immunogenicity, compared with transplanted exogenous MSCs. These reports revealed that MSCs-derived exosomes might promise to be a new and valuable therapeutic strategy for TBI than MSCs themselves. However, the concrete mechanisms involved in the positive effects induced by MSCs-derived exosomes in TBI are still ambiguous. In this review, we intend to explore the potential effects of MSCs-derived exosomes on neuroinflammation and neurogenesis in TBI and, especially, on therapy.